Formulation and Evaluation of Iornoxicam as Dissolving Microneedle Patch - Adeeb R. Alkhiro; Mowafaq M. Ghareeb (College of Pharmacy University of Baghdad, 2020)
The objective of the study was to develop microneedle (MN) patch, with suitable properties to ensure the delivery of a therapeutic level of lornoxicam (LXM) in a period suitable to replace parenteral administration in patients, especially those who fear needles. The used polymers were cold water-soluble polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP) of low molecular weight with PEG 400 as plasticizer and Tween 80 (to enhance the release) using micro molding technique. Patches were studied for needle morphology, drug content, axial fracture force measurement and drug release while the optimized formulas were further subjected to pH measurement, folding endurance, ex vivo permeation study, histopathology study, stability study and compatibility study. The patch with 11:1 ratio of PVA to PVP, 30% solid content, 5% PEG 400 and 3% Tween 80 resulted in axial needle fracture force value of (1.35 N) which is suitable for skin penetration. The release was fast with almost 100% of drug released in 60 minutes. The permeation was enhanced significantly with a steady state flux of about 3.1 times that of the solution. The lag time of MN is shorter in comparison with ordinary patch. Histopathology studies demonstrated the safety of the formulation, both stability studies and compatibility studies showed the suitability of the formulation. The results indicated that LXM microneedle patch could enhance drug permeation while achieving fast and painless administration. Keywords: Microneedle patch, Polyvinyl alcohol, Polyvinylpyrrolidone, Fracture force, Lornoxicam.